Locating Politics in Ethiopia's Irreecha Ritual - Bekele Debele, Serawit, (Studies of Religion in Africa;, 2019)
In Locating Politics in Ethiopia's Irreecha Ritual Serawit Bekele Debele gives an account of politics and political processes in contemporary Ethiopia as manifested in the annual ritual performance. Mobilizing various sources such as archives, oral accounts, conversations, videos, newspapers, and personal observations, Debele critically analyses political processes and how they are experienced, made sense of and articulated across generational, educational, religious, gender and ethnic differences as well as political persuasions. Moreover, she engages Irreecha in relation to the hugely contested meaning making processes attached to the Thanksgiving ritual which has now become an integral part of Oromo national identity.